Performance of new varieties of Cenchrus purpureus, tolerant to drought, during dry period - Arias, R. C.; Ledea, J. L.; Benítez, D.; Ray, J.; Ramírez de la Ribera, J. L. (Cuban Journal of Agricultural Science, 2018)
In order to evaluate the morphological and productive performance of new varieties of Cenchrus purpureus (CT-601, CT-603, CT-605, CT-608, CT-609 and CUBA CT-115 as control), tolerant to drought in different regrowth ages (60, 90, 120, 150 days), in the dry season, a study was developed with a random block design in factorial arrangement, in which the effect of interaction of factors (6x4) on productive and agronomic variables was controlled. Yield of green matter and dry matter, leaf morphology, plant height and number of nodes were affected by the second degree interaction, while thickness and length of the stem were modified by the effects of variety and age, respectively. The highest value of green matter and dry matter yield was obtained in the CT-601 variety, at the age of 150 days (10.6 t GM ha-1 and 2.76 t DM ha-1, respectively) for p≤0.001. For green mater, the values were similar for CT-605 and CT-609, and for DM, only with CT-609, and, in both cases, they were higher than CT-115. The lowest (p≤0,001) mean of Green matter and dry matter was provided by CT-605, during the ages of 60, 90 and 120 days for green matter (1,08; 1,68 and 1,83 t GM ha-1), and 60, 90, 120 and 150 days for DM (0,27; 0,29; 0,41 and 1.97 t DM ha-1). At 120 days, a slight recovery was observed in the accumulation of DM by the CT-115, CT-609, CT-603 and CT-601 varieties, with redundant values of 1.20-1.58 t DM ha-1. It is concluded that, under the conditions of Valle del Cauto, the combined effect of regrowth age with variety conditions the agroproductive performance of the new varieties of Cenchrus purpureus tolerant to drought. Keywords: dry ecosystems, Cenchrus, yield, productivity